Mongolian Meat Cakes (The Biblical archaeology review, 2023)
For this Test Kitchen, we are going a bit further afield, to China’s Yuan Dynasty (1271-1368 CE). Founded by Kublai Khan, grandson of Genghis Khan, the Yuan Dynasty was the successor to the great Mongol Empire founded by Genghis. Our recipe comes from a dietary menu, the Yinshan Zhengyao ("Proper and Essential Things for the […]